Management of Submacula Bleeding with Pneumatic Displacement - Shaelva Lassa Sabatini; AK Ansyori; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2019)
Introduction. Submacular hemorrhage is defined as the presence of blood in the potential space between retinal pigment epithelium (RPE) and neurosensory retinal in the macula. Pneumatic displacement is one of the management procedures that is shifting the bleeding under the macula by injecting gas. The purpose of writing this case report is to report Sub-macula Bleeding cases which are managed with Pneumatic Displacement. Case Presentation. A 55-year-old woman, housewife, was living outside the city, came with complaints of a sudden blurred left eye since 2 weeks ago. At the ophthalmological examination, 612 pH (-) right eye vision and 1/300 left eye vision were obtained. On examination of the anterior segment in the right and left eye the lens is cloudy with grade I nuclear morphology. The image of the right eye fundoscopy is within normal limits, whereas in the left eye a macula is found: reflex fovea (-) blood (+). The choice of therapy in this patient is carried out by Pneumatic Displacement by injecting C3F8 gas, which aims to shift the bleeding under the macula by injecting gas. Conclusion. Pneumatic Displacement is a simple procedure, not too invasive, and the risk of intraocular complications is smaller. Pneumatic Displacement aims to shift blood from under the macula to other parts of the retina that are less vital for vision.